2020
DOI: 10.1016/j.yebeh.2020.106966
|View full text |Cite
|
Sign up to set email alerts
|

Well-being of mothers with epilepsy with school-aged children

Abstract: The purpose of the study was to examine different aspects of well-being in mothers with epilepsy with school-aged children. Methods: In an observational study, mothers, identified from the European Registry of Antiepileptic Drugs and Pregnancy database in the Netherlands, completed questions on epilepsy, the impact of epilepsy on daily functioning, quality of life, behavioral problems, and parenting stress. Descriptive analyses were performed to examine the prevalence of behavioral problems and the impact of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The use of AEDs by women with epilepsy during pregnancy may affect their children's intellectual development in the future. It has been found that the use of VPA by women during pregnancy may affect their children's cognitive functions and lead to IQ decline [9,51]. The use of PHT and PB or polytherapy also has a negative effect on the intellectual development of children of epileptic mothers, while no such negative effect was observed with the use of CBZ [5].…”
Section: Effects Of Aeds Use In Pregnant Women On Their Children's Co...mentioning
confidence: 99%
“…The use of AEDs by women with epilepsy during pregnancy may affect their children's intellectual development in the future. It has been found that the use of VPA by women during pregnancy may affect their children's cognitive functions and lead to IQ decline [9,51]. The use of PHT and PB or polytherapy also has a negative effect on the intellectual development of children of epileptic mothers, while no such negative effect was observed with the use of CBZ [5].…”
Section: Effects Of Aeds Use In Pregnant Women On Their Children's Co...mentioning
confidence: 99%